Side-polished plastic optical fiber coated with nanomaterials for chemical sensing applications - Khalaf, Ahmed Lateef (2017)
Gaseous and liquid pollutants such as ammonia (NH3) gas and ethanol liquid, are ubiquitous in daily human activities and have been extensively studied because of their high toxicity and wide use in many fields. Common NH3 gas and ethanol liquid detectors are electrical based. Although these electrical or conductometric sensors attain high sensitivity, they suffer from drawbacks that include poor selectivity, high operating temperature, and being prone to electromagnetic interference, which can be addressed by optical sensor. Optical fiber sensors present advantages in certain aspects as compared with electrical sensor, such as their compact size, capability to work in harsh environment, and capacity for remote and distributed sensing. However, chemical sensing using optical fiber has not been fully explored. Presently, nanotechnology enabled chemical sensors have been increasingly used to enhance the sensing performance as compared with the conventional sensors toward target analytes owing to their high surface area. The sensing layer based on nanostructures has been identified to work at low temperature with high sensitivity. Therefore, this research project aims to design and comprehensively analyze optical fiber based NH3 gas and ethanol liquid sensors with the incorporation of different nanostructure coatings as sensing layers. Plastic optical fiber (POF) was selected as the transducing platform for the sensor because of its low cost, ease in fabrication, and suitability for remote sensing applications. The sensitivity of POF based sensors can be improved by simply polishing part of the fiber to form side-polished optical fiber (SPPOF) using simple mechanical polishing technique. Thus, the light interaction upon coating with the sensing layer will significantly improve and great absorbance response will be achieved upon exposure to different target chemical concentrations. The influence of nanostructures morphology and roughness on the sensing performance was also studied in this PhD research.The nanostructures under investigation were tungsten oxide (WO3), graphene oxide (GO), and carbon nanotubes (CNTs). Chemically synthesized aluminum oxide (Al2O3)/polyaniline (PANI) and graphene/PANI nanocomposites were also considered as sensing layers. The different nanostructured sensing layers were integrated with the polished area of the POF via radio frequency sputtering and drop-casting deposition techniques. Micro-nano characterization techniques such as SEM, EDX, AFM, Raman spectroscopy and XRD were utilized to obtain detailed structural properties of these nanostructures to fundamentally understand their functionalities with respect to the optical sensor performance. The response of the sensors towards target chemicals at different concentrations was measured using absorbance change within the wavelength range of 400 – 800 nm at room temperature. The sensing performance was evaluated in terms of response time, recovery time, sensitivity, and repeatability. The chemical sensing performance of the developed SPPOF sensors was compared with the performance of another modified fiber, which is uncladded POF (UCPOF), using absorbance measurement. The optical sensing mechanisms of the analyte molecules and nanostructured sensing layer coated onto the polished fiber region towards NH3 and ethanol with concentrations of 0.125% – 1% and 20% – 100%, respectively, at room temperature were explained. For the first time, according to the author’s knowledge, an SPPOF NH3 sensor coated with sputtered gold (Au)/WO3 nanostructure thin films was successfully developed. The obtained sensitivity, response time and recovery time were 29.26/vol%, 1.2 min, and 7.3 min, respectively. Novel NH3 sensor based on SPPOF coated with graphene/PANI nanocomposite demonstrated significant sensitivity of 55.47/vol%. The remote sensing performance of the developed SPPOF sensors was also investigated by connecting them to 1.1 km multimode silica optical fiber. The SPPOF remote sensors coated with graphene/PANI and CNT exhibited excellent sensitivities of 16.63/vol% and 0.23/vol% toward different concentrations of NH3 and ethanol, respectively, at room temperature with high selectivity and long shelf life. The developed chemical sensors using SPPOF coated with nanomaterials showed superior performance as compared with the electrical based sensors. The excellent sensing performance of the optical fiber sensors via low cost and simple techniques indicates its high efficiency for remote chemical sensing in various industrial and environmental applications.